The viability of a National Retrenchment Scheme (NRS) in Malaysia - Ali Mohamed, Ashgar Ali; Sardar Baig, Farheen Baig (The Malaysian Current Law Journal Sdn Bhd, 2015)
Through this article, the writers have laid down the reasons why the Employers’ Federation was not initially in favour of such a fund,reasoned out some of their contentions against it, and stated how the Fund would benefit them in the long run and serve as a protection to them in times of economic uncertainty. Further, some suggestions were formulated in relation to the mechanism of the National Retrenchment Scheme, with reference to the views of the prominent scholar, Al-Marhum Professor Harun Hashim, and some guidelines that could be taken and followed from the National Insurance Fund of the United Kingdom. What is being emphasised is that workers who are terminated from employment due to redundancy in an organisation, should not be made to suffer further by not being paid their retrenchment compensation provided by the 1980 Regulations and/or the collective agreement to which the affected worker was formally a member of.